Respuestas

2013-08-17T21:01:43+02:00
Moni,
Te respondo las dos primeras

3(a^2 - b^2) - 5z(b^2 - a^2)
= 3(a^2 + b^2) + 5z(a^2 - b^2)
= (a^2 - b^2)(3 + 5z)
3(a^2 - b^2) - 5z(b^2 - a^2) = (a + b)(a - b)(3 + 5z)  
                                               EXPRESIÓN FINAL


30(x + y)^2(a - b) + 18(x + y)(a - b)^2
6(x + y)(a - b)[5(x + y) + 3(a + b)]
30(x + y)^2(a - b) + 18(x + y)(a - b)^2 = 6(x + y)(a - b)(5x + 5y + 3a + 3b)
                                                                   EXPRESIÓN FINAL